Peran Instagram Reels dalam Strategi Digital Public Relations Event Megabuild 2025 - Virlinda, Alicia; Candraningrum, Diah Ayu (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2026)
In the digital era, social media has become an important medium for organizations to build relationships with audiences through Digital Public Relations. This study aims to examine the role of Instagram Reels in the Digital Public Relations strategy of Megabuild Indonesia 2025, particularly in facilitating audience engagement. This research is grounded in Excellence Theory with a Two-Way Symmetrical Communication approach, the concept of Digital Public Relations, and audience engagement theory. A qualitative approach with a case study method was applied in this study. Data were collected through in-depth interviews with the organizing team and event participants, observation of Instagram Reels content, and analysis of internal documentation from the Megabuild Public Relations team. The findings indicate that Instagram Reels function as a two-way communication medium that enables audience participation through digital interactions and contributes to the formation of awareness and positive perceptions of Megabuild Indonesia 2025. The use of interactive and storytelling-based content encourages dialogic audience engagement. These findings suggest that content variability and the utilization of audience feedback play a crucial role in audience-oriented Digital Public Relations practices. Di era digital, media sosial dimanfaatkan oleh organisasi sebagai sarana untuk membangun hubungan dengan audiens melalui praktik Public Relations digital. Penelitian ini bertujuan untuk mengkaji peran Instagram Reels dalam strategi Public Relations digital pada kegiatan Megabuild Indonesia 2025, khususnya dalam membangun keterlibatan audiens. Penelitian ini menggunakan teori keunggulan dengan pendekatan komunikasi dua arah simetris, konsep Public Relations digital, serta konsep keterlibatan audiens sebagai landasan teoretis. Pendekatan kualitatif dengan metode studi kasus diterapkan dalam penelitian ini. Pengumpulan data dilakukan melalui wawancara mendalam dengan tim penyelenggara dan partisipan kegiatan, observasi terhadap konten Instagram Reels, serta dokumentasi internal tim Public Relations Megabuild. Hasil penelitian menunjukkan bahwa Instagram Reels berperan sebagai media komunikasi dua arah yang memfasilitasi partisipasi audiens melalui interaksi digital serta membentuk kesadaran dan persepsi positif terhadap kegiatan Megabuild Indonesia 2025. Penyajian konten yang interaktif dan berbasis penceritaan mendorong keterlibatan audiens secara dialogis. Temuan ini menunjukkan bahwa pengelolaan konten yang variatif serta pemanfaatan respons audiens menjadi bagian penting dalam praktik Public Relations digital yang berorientasi pada audiens.